Clinical Presentations of Deviated Nasal Septum and Mladina’s Classification - Thakur, Sanjeev Kumar; Yadav, Baleshwar; Bedajit, Raj Kumar; Anwar, Afaque (Journal of Chitwan Medical College, 2019)
Background: Nasal Septal deviation is a frequently found entity in ENT OPD. The objective of the study was to describe the clinical presentations of deviated nasal septum, classify them according to the Mladina’s system and find out the relation of trauma with the type of septal deviation. Methods: One hundred fifty cases of septal deviation were classified according to Mladina’s classification, after thorough interview, nasal examination and nasal endoscopy. Data were analyzed with SPSS version 21, after tabulation. Chi-square test was applied as the test of significance. Results: Out of 150 cases of septal deviation, Male 82 (54.6%) outnumbered the female patients 68 (45.3%). Most of these patients were of second and third decade (20-40 years age group). The most common presenting complaint was that of nasal obstruction 121(80.6%), headache68 (45.3%) and nasal discharge52(34.6%). 78(52%) of patients revealed history of trauma. Type II 32 (21.3%) and Type V 31 (20.6%) were the commonest followed by Type III 24(16%). Conclusions: Nasal septal deviation is a common presentation in ENT OPD. Mladina’s classification found Type II and Type V to be quite common. Nasal obstruction, headache and rhinorrhea are frequent associated complaints. Nasal endoscopy is very important for the diagnosis, especially of posterior deflections.